SEGMENTASI CITRA UNTUK MENGENALI TEKSTUR UIS KARO DENGAN METODE FILTER GABOR - Rulo Sembiring; Pilipus Tarigan (UPPM, 2020)
With the development of image processing, humans are competing to produce an attractive image from existing simple images. In addition, according to the development of time, image processing is increasingly becoming a necessity for many people, especially in the arts, making films as a special effect on images. One of the image processing that is currently popular and widely used in the world of film or art is image. The process of the Gabor filter method is the process of creating an effect or adding a gray level, where an object will be slowly converted into a recognizable object.